Analisis index kerusakan Jalan Rigid Pavement dengan metode Pavement Condition Index (PCI) pada Jalan Lebaksono – Jalan Purwojati Ngoro, Kabupaten Mojokerto - Subekti , Yogi Dwi; Tjendani , Hanie Teki (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The lebaksono - purwojatingoro mojosari city is an industrial road. Various heavy and light vehicles pass through the road, causing road damage. Evaluation of road damage conditions is needed to monitor the level of road damage that occurs on a road section. This study aims to determine the level of damage that occurs. The method used in assessing the condition of this pavement damage is the PCI (Pavement Condition Index) method, conducting a visual survey by viewing and analyzing damage based on the type, level of damage and quantity of damage to serve as the basis for carrying out maintenance and repair activities. . The results of evaluating the condition of the lebaksono - purwojatingoro road section using the PCI method obtained divided slab damage (26.2%), patching small (7.82%), spalling corner (5.07%), shrinkage cracks (0. 85%), line crack (17.18%), spalling joint (4.79%), patching large (22.82%), punchout (0.85%), corner break (10.42), joint seal (1.13%), durability crack (0.85%), blow up / buckling (0.28%), popout (1.69%).